Butser Ancient Farm: An Internship Full of Senses - Àngels Fernández Canals (EXARC Journal)
‘What is experimental archaeology?’ people asked me. ‘But if you work within an experimental place, you won’t be able to put into practise the tools learned in your Masters about cultural heritage and museology’ said some of my classmates. However, for me it was really important to do my internship in a place where the archaeology was paramount; at the same time, I was interested in a site where there was an active and thriving education department. It is for these reasons that Butser Ancient Farm was the perfect choice to put into practice my interests: archaeology and education.